Desarrollo de un entorno virtual 3d de un proceso batch de llenado y sellado de botellas mediante hardware in the loop - Andi Aguinda, Dennis Cristhian (2022)
The current project is aimed virtual environment development, through the Unity 3D graphics engine, where the filling and sealing bottles simulation of a batch process of filling and sealing bottles batch process simulation, through "Hardware In The Loop", further, it will be used a programmable logic controller for the automation of this process. The process simulation within the environment consists of 5 stages, which are as following, first stage 1 container dispenser, second stage 2 liquid dispenser, third stage container sealing, fourth stage quality control area and finally, the fifth stage 5 final product classification